2019
DOI: 10.1159/000496393
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Age-Related Macular Degeneration in the Central Region of Portugal: The Coimbra Eye Study – Report 5

Abstract: Purpose: To describe the 6.5-year incidence and progression of age-related macular degeneration (AMD) in a coastal town of central Portugal. Methods: Population-based cohort study. Participants underwent standardized interviews and ophthalmological examination. Color fundus photographs were graded according to the International Classification and Grading System for AMD and ARM. The crude and age-standardized incidence of early and late AMD was calculated, and progression was analyzed. Results: The 6.5-year cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…While AMD is common in males and females, some studies suggest that female sex is associated with a higher progression rate to early AMD (OR 2.2), and late AMD (HR 1.6–2.6), especially nAMD (HR 1.6–2.1) . However, other studies describe a lack of association between sex and disease progression . A possible explanation for these conflicting results between studies might be attributed to a difference in follow‐up and the greater life expectancy of females .…”
Section: Demographic and Environmental Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…While AMD is common in males and females, some studies suggest that female sex is associated with a higher progression rate to early AMD (OR 2.2), and late AMD (HR 1.6–2.6), especially nAMD (HR 1.6–2.1) . However, other studies describe a lack of association between sex and disease progression . A possible explanation for these conflicting results between studies might be attributed to a difference in follow‐up and the greater life expectancy of females .…”
Section: Demographic and Environmental Risk Factorsmentioning
confidence: 99%
“…There are many modifiable and non‐modifiable risk factors that have been linked to increased risk of the progression of AMD. As the name already suggests, age is the most important demographic risk factor for AMD . A recent meta‐analysis, combining data of 14 population‐based studies, showed an increase in the prevalence of early AMD from 3.5% in people aged 55–59 years up to 17.6% in people 85 years and older.…”
Section: Demographic and Environmental Risk Factorsmentioning
confidence: 99%
“…Age-related macular degeneration is a complex retinal disorder and the leading cause of severe blindness in the elderly population, resulting from both environmental and genetic risk factors [ 178 180 ]. AMD affects central vision and its pathobiology includes activation of the innate immune response, neovascularisation, oxidative stress and a build-up of proteins and lipids [ 179 , 181 ].…”
Section: Pink1/parkin In Neurodegenerationmentioning
confidence: 99%
“…In Europe, few population-based prospective studies have been conducted and differed in diagnostic parameters and study design. The Rotterdam Eye Study in the Netherlands and the Coimbra Eye Study in Portugal assessed the 6.5 year cumulative incidence of early and late AMD, while the AGES-R study in Iceland, the POLA and the ALIENOR studies in France and the Copenhagen City Eye Study included a 5-, 3-4-year and 14-year follow-up, respectively [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%